TYPES OF PAIN IN RHEUMATOID ARTHRITIS: CENTRALIZATION MECHANISMS, RISK FACTORS, AND TREATMENT APPROACHES - Natalia Musialik; Maciej Magiera; Barbara Starosta; Monika Pelczar; Bartosz Brzychcy; Karolina Brzychcy; Karolina Paks; Zuzanna Gajda; Ewa Jench (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and aim: One of the main complaints in rheumatoid arthritis (RA) is pain. It may result not only from inflammation and joint damage, but also from neuropathy and central sensitization, leading to nociplastic (central) pain. This type of pain is often overlooked, as it does not correlate with visible musculoskeletal pathology. Its pathogenesis is not fully understood, and both diagnosis and treatment are challenging. The aim of this paper is to review the types of pain in RA, with a particular focus on nociplastic pain—its causes, clinical presentation, diagnostics, and therapy. Materials and Methods: A review of the available scientific literature on RA was conducted using PubMed, Google Scholar, and Embase databases. Conclusion: Pain in RA can be nociceptive, neuropathic, or nociplastic. Nociplastic pain is driven by central sensitization, influenced by cytokines (IL-1, IL-6, TNF-α), microglial activation, and synaptic transmission imbalance. Diagnosis relies on questionnaires (e.g., Central Sensitization Index – CSI) and sensory testing (e.g., Quantitative Sensory Testing – QST). Treatment includes pharmacological options (paracetamol, benzodiazepines, opioids, SNRIs, naltrexone, TNF-α inhibitors, pregabalin, gabapentin, Sarilumab, JAK1/JAK2 inhibitors) and non-pharmacological methods: pain neuroscience education (PNE), cognitive behavioral therapy (CBT), stress reduction, and tailored physical activity.